PERAN USAHA MIKRO KECIL MENENGAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Niliwati, Baiq; Cahyani, Mimi; Milania Ulpah, Baiq Rizka (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2025)
Central Lombok Regency is one of the regencies in West Nusa Tenggara Province and is a Special EconomicZone (KEK) with tourism destinations. The potential for developing MSMEs in Central Lombok is very large.The number of MSMEs owned is around 8,095 units spread across 12 sub-districts. One of them is Pujut subdistrict with 1,045 MSME units including in Ketara Village. The existence of the Mandalika InternationalCircuit has an impact on the emergence of MSME actors in Ketara Village. So that many people have switchedprofessions from farmers to MSME actors. This study tries to find the impact of MSMEs on the welfare of theKetara Village community and what factors influence the implementation of these MSMEs. This study uses adescriptive qualitative method and data analysis with data reduction. The results of the study and discussionshow that the role of MSMEs in improving community welfare has a very big impact, this can be seen from theincrease in the stages of community welfare before and after opening an MSME business. The presence ofMSMEs in Ketara Village has opened up new jobs and absorption of workers who are currently active as MSMEactors in the production sector as the conclusion of this study. Government support in the development ofMSMEs is very much needed and the inhibiting factors are lack of capital and business networks that need tobe expanded as suggestions and conclusions of this study.